Institutional constraints and digital exports: Evidence from multi-country firm-level data - Phuong, Do Manh (Edelweiss Applied Science and Technology, 2025)
This paper examines how institutional constraints influence firms’ participation in digital exports. It aims to identify which types of institutional barriers most hinder firms’ ability to engage in digital trade and how these effects vary across firm characteristics. Using a novel multi-country firm-level dataset from the World Bank Enterprise Surveys, the study measures digital exports as goods sold electronically and delivered via mail or courier services. Institutional constraints are defined based on firms’ self-assessments of four major obstacles: corruption, political instability, tax administration, and business licensing. To address potential endogeneity, the analysis employs the Entropy Balancing technique. The results indicate that institutional constraints significantly decrease the likelihood of firms engaging in digital exports, with political instability and business licensing emerging as the most detrimental factors. The negative effects are particularly pronounced among large and financially unconstrained firms, which are more exposed to institutional inefficiencies due to their operational scale and digital capacity. While the study draws on a large cross-country dataset, it captures firms’ perceptions rather than objective measures of institutional quality. Future research could incorporate longitudinal data or complementary macro-level indicators to enhance causal inference. This study contributes to the emerging literature on digital trade by integrating institutional quality into firm-level analyses of digital exports. It provides new empirical evidence on how specific institutional barriers constrain digital export participation, offering policy insights for strengthening the institutional foundations of the digital economy.